Pengaruh Dimensi Pelayanan Terhadap Kepuasan Yang Berdampak Pada Loyalitas Nasabah PT BPR Ukabima Nindya Raharja Wonosari Gunungkidul - Sudaryanti, Sudaryanti (STIE AUB Surakarta)
This study aims is to determine the effect of the dimension of service to the satisfaction of the impact on customer loyalty PT BPR Ukabima Nindya Raharja Wonosari. Gunungkidul. This study is a survey research. The data used is primary data by sampling sample in this study was 100 customers. Sampling techniques in this study using a random sampling method used analytical tool Test Instrument Research, Testing linearity, path analysis and regression with t test, F test and R2 test. T test results showed that Tangible has not a significant effect on customer satisfaction. Reliability has not a significant effect on customer satisfaction. Responsiveness has a significant effect on customer satisfaction. Guarantee has a significant effect on customer satisfaction. Attention has a significant effect on customer satisfaction. Tangible has a significant effect on loyalty. Reliability has a significant effect on loyalty. Responsiveness has a significant effect on loyalty. Guarantee has a significant effect on loyalty. Attention has a significant effect on loyalty. Customer satisfaction has a significant effect on loyalty. R2 total value of 91.9% This means that customer loyalty was explained by Tangible, reliability, responsiveness, assurance, attention and customer satisfaction as an intervening variable of 91.9% and the remaining 8.1% described other variables outside the model study. Test results simultaneously (F Test) can be concluded that Tangible, reliability, responsiveness, assurance, attention, customer satisfaction have a significant effect on loyalty. Guarantee direct path was the path most effectively increase loyalty, because it has the greatest impact, positive and significant.Keywords: dimensions of service, satisfaction, and customer loyalty.